Imaging proteins in live mammalian cells with biotin ligase and monovalent streptavidin. - Howarth, M; Ting, A (2008)
This protocol describes a simple and efficient way to label specific cell surface proteins with biophysical probes on mammalian cells. Cell surface proteins tagged with a 15-amino acid peptide are biotinylated by Escherichia coli biotin ligase (BirA), whereas endogenous proteins are not modified. The biotin group then allows sensitive and stable binding by streptavidin conjugates. This protocol describes the optimal use of BirA and streptavidin for site-specific labeling and also how to produce BirA and monovalent streptavidin. Streptavidin is tetravalent and the cross-linking of biotinylated targets disrupts many of streptavidin's applications. Monovalent streptavidin has only a single functional biotin-binding site, but retains the femtomolar affinity, low off-rate and high thermostability of wild-type streptavidin. Site-specific biotinylation and streptavidin staining take only a few minutes, while expression of BirA takes 4 d and expression of monovalent streptavidin takes 8 d.